Nobody Hugs a Cactus - Goodrich, Carter (New York Simon & Schuster Books for Young Readers, 2019)
Hank, a cactus who is as prickly on the inside as he is on the outside, decides he wants a hug.
Keywords: Cactus -- Fiction; Mood (Psychology) -- Fiction; Tumbleweeds -- Fiction; Animals -- Fiction; Hugging -- Fiction